20(S)-Ginsenoside Rg2 attenuates myocardial ischemia/reperfusion injury by reducing oxidative stress and inflammation: role of SIRT. Issue 42 (2nd July 2018) - Fu, Wenwen; Xu, Huali; Yu, Xiaofeng; Lyu, Chen; Tian, Yuan; Guo, Minyu; Sun, Jiao; Sui, Dayun
Abstract : 20( S )-Ginsenoside Rg2 confers a protective effect against MI/R injury via SIRT1 signaling, by alleviating oxidative stress and reducing myocardium inflammation. Abstract : Previously we demonstrated that 20( S )-ginsenoside Rg2 protects cardiomyocytes from H2 O2 -induced injury by inhibiting reactive oxygen species (ROS) production, increasing intracellular levels of antioxidants and attenuating apoptosis. We explored the protective effect of 20( S )-ginsenoside Rg2 on myocardial ischemia/reperfusion (MI/R) injury and to clarify its potential mechanism of action. Rats were exposed to 20( S )-ginsenoside Rg2 in the presence/absence of the silent information regulator SIRT(1) inhibitor EX527 and then subjected to MI/R. 20( S )-Ginsenoside Rg2 conferred a cardioprotective effect by improving post-ischemic cardiac function, decreasing infarct size, reducing the apoptotic index, diminishing expression of creatine kinase-MB, aspartate aminotransferase and lactate dehydrogenase in serum, upregulating expression of SIRT1, B-cell lymphoma-2, procaspase-3 and procaspase-9, and downregulating expression of Bax and acetyl (Ac)-p53. Pretreatment with 20( S )-ginsenoside Rg2 also resulted in reduced myocardial superoxide generation, gp91 phox expression, malondialdehyde content, cardiac pro-inflammatory markers and increased myocardial activities of superoxide dismutase, catalase and glutathione peroxidase. These results suggested that MI/R-induced oxidative stress and inflammation were attenuated significantly by 20( S )-ginsenoside Rg2. However, these protective effects were blocked by EX527, indicating that SIRT1 signaling may be involved in the pharmacological action of 20( S )-ginsenoside Rg2. Our results demonstrated that 20( S )-ginsenoside Rg2 attenuates MI/R injury by reducing oxidative stress and inflammatory responses via SIRT1 signaling.